(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
We are trying to improvise the existing Round Robin Algorithm and test its performance across host OS and VM as well. We would be testing the performance of the improvised algorithm on the Cent OS running on Virtual Box.. We have worked on the scheduling algorithm specifically Round Robin Scheduling in our lab classes. Basically, we will be finding out the best way to properly select the “Time Quantum” so as to get Minimum ‘Waiting Time’ and ‘Turnaround Time’.After looking into so many research papers, we have found that, by sorting the processes in increasing order of their burst time and taking median of all the burst time, we can minimize the waiting and turnaround time.